Maternal and peri-natal outcomes of dengue fever with special emphasis on vertical transmission - Naz, Saima; Ghafoor, Farkhanda; Mukhtar, Shafqat; Tayyaba Rahat (Journal of the Pakistan Medical Association, 2022)
Objectives: To investigate the maternal and peri-natal outcomes of dengue infection and frequency of dengue immunoglobulin G positivity in pregnant women along with pregnancy outcomes. Method: The observational two-phase study was conducted from 2012 to 2015 in Lahore, Pakistan. I In phase 1, pregnant women who had acute dengue fever were prospectively and retrospectively enrolled from 4 tertiary care hospitals. Demographic data, clinical/laboratory parameters and maternal/foetal outcomes were recorded for each subject. In the second phase, normal pregnant women with no current or past history of dengue fever were enrolled from Gynaecology Department of Shaikh Zayed Hospital, Lahore, to determine the frequency of dengue immunoglobulin G positivity and pregnancy outcome. Data was analysed using SPSS 20. ---Continue